Implementasi Model Project-Based Learning Pada Mata Pelajaran Pemograman dan Aplikasi Mikrokontroler di Sekolah Menengah Kejuruan - Habibullah, Habibullah; Saputri, Rani (Jurnal Pendidikan Teknik Elektro, 2025)
This research aims to determine student learning outcomes after implementing the Project-Based Learning model in programming and microcontroller application subjects at SMK Negeri 1 Koto XI Tarusan. This type of research is initial experimental research (Pre-Experiment) with a one-group pretest posttest design. The research subjects were students of class XI Electronic Engineering at SMK Negeri 1 Koto XI Tarusan for the 2024/2025 academic year, totaling 26 students. The research results show that the use of the Project-Based Learning model can improve student learning outcomes. These results are seen from the psychomotor domain in the form of skills assessment sheets and student learning outcomes assessments in the form of pretests and posttests. Based on data analysis analyzed using the N-Gain Score formula, a result of 0.45 was obtained, which is included in the medium category. The pretest results obtained were 34.61% in the low category, the posttest results obtained were 84.61% in the very high category and the skill results obtained were 92% in the very skilled category. In this way, the Project-Based Learning learning model improves student learning outcomes in the subjects of programming and microcontroller applications.